Métodos de superação de dormência: qualidade fisiológica e sanitária e transmissão de Alternaria alternata em sementes de Lithrea molleoides e Senna macranthera - Piveta, Graziela (2009)
This work was carried out with seeds of Senna macranthera and Lithrea molleoides objective was to determine the health and physiological quality of seed through different tests and to evaluate the transmission of Alternaria alternata and its influence on health and physiological quality of seeds after submission of methods to overcome dormancy. Evaluations of health, germination, seedling growth, accelerated aging, electrical conductivity and tetrazolium test, seeds were submitted to overcome dormancy, by: acid scarification for 10, 15.20 and 25 minutes, soaking in hot water, with temperatures of 70, 80 and 900C to cool for 24 hours, soaking in gibberellic acid (GA3) at concentrations of 250 and 500 mg / l for 24 and 48 hours, immersion in potassium nitrate (KNO3), the concentration of 0,2% for 24 and 48 hours. Seed was inoculated in A. alternata by the method of suspension of spores. The suspension of spores was standardized at 104 spores/ml using a Neubauer chamber. The inoculation of seeds was performed by immersion for three time periods (24, 48 and 72 hours). Then were made: health, germination and growth of seedlings, the nursery was evaluated the rate of speed of emergence and seedling health. L. molleoides showed higher percentage of germination when it was subjected to scarification acid for 20 minutes and hot water at 700C, and when used S. macranthera acid scarification for 15 and 20 minutes and soaking in GA3 250 and KNO3 for 48 hours. The occurrence of A. alternata in seedlings, indicates that this fungus can be transmitted by seed for both species.